Structural Optimization of the Vortex Finder in Cyclone Separators of Circulating Fluidized Bed Boiler - Zhao Hancheng (Jurnal Syntax Transformation, 2026)
Circulating Fluidized Bed (CFB) boilers are widely applied in industrial power generation due to their fuel flexibility, combustion efficiency, and lower pollutant emissions. However, the vortex finder component in cyclone separators frequently experiences excessive thermal expansion, structural deformation, and performance degradation due to high-temperature exposure, thermal stresses, and continuous particle erosion. These issues can reduce cyclone separation efficiency and compromise the reliability of the overall boiler system. This study aims to develop an integrated structural optimization design for the vortex finder to improve its thermal, mechanical, and operational reliability under harsh CFB boiler operating conditions. The research employed an applied engineering approach that combined failure analysis, finite element analysis (FEA), computational fluid dynamics (CFD) simulations, prototype testing, and field verification. The results revealed that excessive expansion was primarily caused by inadequate expansion compensation, rigid support constraints, and combined thermal-mechanical loading conditions. The proposed optimization scheme, including the use of high-temperature alloy materials, ceramic coatings, flexible expansion joints, redesigned support structures, optimized vortex finder geometry, and improved sealing systems, effectively reduced thermal stress, maintained vortex stability, and enhanced wear resistance. Experimental and field validation confirmed improved structural integrity and sustained cyclone separation performance during operation. In conclusion, the integrated optimization approach provides an effective engineering solution for mitigating vortex finder failure and improving the service life and reliability of cyclone separators in CFB boiler systems.